2015
DOI: 10.1016/j.nut.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance vector analysis, phase-angle assessment and relationship with malnutrition risk in a cohort of frail older hospital patients in the United Kingdom

Abstract: ObjectiveBioelectrical impedance vector analysis (BIVA) and phase angle (PA) have been shown previously to indicate relative nutritional status in patients. The aim of this study was to investigate the application of BIVA and PA assessments in a cohort of frail older hospital patients and compare these assessments with malnutrition risk screening by MUST (Malnutrition Universal Screening Tool), and the MNA-SF® (Mini-Nutritional Assessment-Short Form). MethodsSixty-nine patients (n = 44 men; n = 25 women; age 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 25 publications
5
37
1
1
Order By: Relevance
“…This cutoff coincided with the lowest tertile of PA (<4.5°). These values are in keeping with previous estimates showing that the mean PA in frail geriatric patients is ≈4.5° in women and 4.6° in men,29, 30 and that the optimal PA cutoff for detection of sarcopenia is 4.5° 17. By contrast, the mean PA in healthy geriatric patients has previously been reported as 6.2° in men and 5.6° in women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This cutoff coincided with the lowest tertile of PA (<4.5°). These values are in keeping with previous estimates showing that the mean PA in frail geriatric patients is ≈4.5° in women and 4.6° in men,29, 30 and that the optimal PA cutoff for detection of sarcopenia is 4.5° 17. By contrast, the mean PA in healthy geriatric patients has previously been reported as 6.2° in men and 5.6° in women.…”
Section: Discussionsupporting
confidence: 91%
“…Despite being more prevalent in malnourished patients, a low PA has been shown to have poor specificity for predicting malnutrition 36, 37. Previous studies showed only a borderline significant correlation between PA and Mini Nutritional Assessment Short Form score and no correlation with the Malnutrition Universal Screening Tool score 29. The low prevalence of malnutrition in our population (3% as defined by Mini Nutritional Assessment Short Form ≤7) and the short‐form screening tool used may have limited the power of this study to detect a significant association with PA.…”
Section: Discussioncontrasting
confidence: 62%
“…In a recent study, Basile et al (60) reported independent effects of grip strength and skeletal muscle mass on phase angle measured in a cohort of elderly adults; low phase angle was associated with reduced grip strength. Slee et al (61) evaluated a cohort of frail older hospitalised patients, some of whom were malnourished, and observed a low phase angle compared with healthy elderly reference values (61) . Age-related changes in other BIA resistance and reactance ratios and combinations at different frequencies are also recognised.…”
Section: Bioimpedance Analysismentioning
confidence: 99%
“…Therefore, the PhA has been proposed as a parameter to predict clinical outcomes and mortality for several diseases . In addition, several studies have considered it an important nutrition assessment tool . However, the usefulness of this parameter as a sarcopenia marker has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%